Transfusion and component characteristics are not associated with allergic transfusion reactions to apheresis platelets - Savage, William J. (Transfusion, 2014)
BACKGROUND: Transfusion-related characteristics have been hypothesized to cause allergic transfusion reactions (ATRs) but they have not been thoroughly studied. The primary objective of this study is to evaluate the associations of infusion rate, infusion volume, ABO mismatching, component age, and premedication with the incidence and severity of ATRs. A secondary objective is to compare the risk of these attributes relative to the previously reported risk factor for aeroallergen sensitization in transfusion recipients, as measured by an aeroallergen-specific IgE antibody screen. STUDY DESIGN AND METHODS: Clinical and transfusion-related data were collected on subjects with reported ATRs and uneventful (control) apheresis platelet transfusions over a combined 21 month period at two academic medical centers. Control transfusions were selected as the next uneventful transfusion after an ATR was reported. Logistic regression, Mann-Whitney and t tests were used to assess associations with ATRs. Previously reported aeroallergen-specific IgE screening data was incorporated into a multivariable logistic regression. RESULTS: 143 ATRs and 61 control transfusions were evaluated among 168 subjects, ages 2-86 years. Infusion rate, infusion volume, ABO mismatching, component age, and premedication showed no statistically significant association with ATRs (P>0.05). Neither infusion rate nor infusion volume increased the risk of anaphylaxis vs. mucocutaneous only ATRs. Aeroallergen sensitization has previously been associated with ATRs. After controlling for transfusion-related covariates, aeroallergen sensitization remained statistically significantly associated with ATRs (OR 2.68, 95%CI: 1.26-5.69). CONCLUSIONS: Transfusion and component-specific attributes are not associated with ATRs. An allergic predisposition in transfusion recipients is associated most strongly with ATR risk.